Leadership Policies and Personal Competence of Sports Leaders in Aceh Province: A Qualitative Study - Amir, Nyak; Maulana, Riyan; Ahadin, Ahadin; Yahya, Muhammad (Journal Public Policy, 2025)
This study aims to analyze the leadership policies and personal competencies of sports officials in Aceh Province, Indonesia. The research adopts a qualitative descriptive approach, involving 10 key informants selected through purposive sampling, including deputy regents, heads of departments, and education officers with backgrounds in sports. Data were collected through observation and in-depth interviews, then analyzed using data reduction, data display, and verification techniques. The findings reveal that sports community members who occupy leadership positions in Aceh demonstrate strong cognitive, affective, and psychomotor competencies. Their leadership styles are a combination of various models, including democratic, participatory, administrative, and charismatic approaches. Respondents emphasize discipline, teamwork, and alignment with institutional goals while also integrating local cultural values in decision-making and leadership behavior. The study concludes that sports-based leadership in Aceh is shaped by both educational background and sports experiences, which enhance strategic thinking, policy-making skills, and leadership effectiveness. This finding challenges the public perception that such leaders attain positions through favoritism or coincidence. The study contributes to the understanding of how sports experience can foster effective leadership in public administration.